11th Annual MEMS Conference - Reshaping the Minerals and Metals Industry - Lisa Morrison (Society for Mining, Metallurgy & Exploration, 2002)
The 11th Annual Mineral Economics and Management Society (MEMS) conference was held April10-12, 2002, in Montreal, Quebec. It consisted of a series of technical sessions. Each paper addressed the economic issues that are related to the changes that many people believe are now required in the mining industry. Some of the papers were directed at how the mining industry will handle the changes that will be required in its philosophy and operations management. Of equal importance was whether the industry possesses the toolkit necessary to effect these changes and emerge stronger from its challenges.